2017
DOI: 10.3389/fimmu.2017.00586
|View full text |Cite|
|
Sign up to set email alerts
|

Specific Antibody Deficiency: Controversies in Diagnosis and Management

Abstract: Specific antibody deficiency (SAD) is a primary immunodeficiency disease characterized by normal immunoglobulins (Igs), IgA, IgM, total IgG, and IgG subclass levels, but with recurrent infection and diminished antibody responses to polysaccharide antigens following vaccination. There is a lack of consensus regarding the diagnosis and treatment of SAD, and its clinical significance is not well understood. Here, we discuss current evidence and challenges regarding the diagnosis and treatment of SAD. SAD is norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(54 citation statements)
references
References 46 publications
1
51
0
2
Order By: Relevance
“…Similar to specific antibody deficiency (SAD) ( 105 ), poor humoral immune responses are observed in most BENTA patients in response to T cell-independent vaccines such as pneumococcal and meningococcal polysaccharide vaccines, even with repeated boosts. Some patients also fail to mount lasting protective titers to T cell-dependent conjugate vaccines for pneumococcal bacteria (i.e., Prevnar), varicella-zoster virus (VZV), or measles.…”
Section: Card11mentioning
confidence: 99%
“…Similar to specific antibody deficiency (SAD) ( 105 ), poor humoral immune responses are observed in most BENTA patients in response to T cell-independent vaccines such as pneumococcal and meningococcal polysaccharide vaccines, even with repeated boosts. Some patients also fail to mount lasting protective titers to T cell-dependent conjugate vaccines for pneumococcal bacteria (i.e., Prevnar), varicella-zoster virus (VZV), or measles.…”
Section: Card11mentioning
confidence: 99%
“…2,3 The diagnosis of SAD requires the documentation of an adequate response to polysaccharide antigens measured by immune response to the 23-polyvalent pneumococcal vaccine (Pneumovax®, 23-PPV) and exclusion of other causes of immunodeficiency. 4,5 Measurement of antibody responses to all serotypes in 23-PPV may not be available in all facilities, and thus, a limited set of pneumococcal serotypes are often used to diagnose SAD. 6 Based on previous studies that demonstrated differences in the immunogenicity among pneumococcal serotypes, 7,8 we hypothesized that a narrower panel of serotype-specific antipneumococcal antibody titers would provide comparable diagnostic utility for SAD diagnosis as the complete panel of 23 serotypes.…”
Section: Using Only a Subset Of Pneumococcal Serotypes Is Reliable Fomentioning
confidence: 99%
“…45,46 Systemic, invasive, or opportunistic infections are uncommon. 47 If warranted by the frequency and severity of infections, patients with SAD may be managed with prophylactic antibiotics or Ig replacement therapy.…”
Section: Specific Antibody Deficiencymentioning
confidence: 99%